Effect of dietary fats on endogenous oleic acid biosynthesis in rat liver - Levitsky, A.; Velichko, V.; Selivanskaya, I.; Lapinskaya, A. (Journal of Education, Health and Sport, 2022)
Aim: Determine the effect of dietary fats with different fatty acid composition on the biosynthesis of oleic acid and its metabolic precursors in the liver . Methods: High linoleic sunflower oil (HLSO), high oleic sunflower oil (HOSO) and palm oil (PO) were used. Rats were fed a semi-synthetic fat-free diet (FFD) and fat diets containing 5 % of the above oils (instead of starch) for 30 days. Liver lipids were divided into 3 fractions: neutral lipids (NL), phospholipids (PL) and free fatty acids (FFA). The fatty acid composition of the fractions was determined by gas chromatography. The “activity” of fatty acid synthase was determined from the total content of the products of this reaction (C16:0 and C16:1). The “activity” of palmitic acid elongase was determined by the ratio С18:0/С16:0, as well as by the formula (С18:0+С18:1)/(С16:0–С16:1). The “activity” of stearic acid desaturase (SCD1) was determined by the ratio C16:1/C16:0 (SCD16) and by the ratio C18:1/C18:0 (SCD18). Results: In rats treated with fat diets, the content of palmitic and oleic acids is reduced only in the NL fraction, and to the greatest extent when consuming the diet with HLSO. The “activity” of palmitic acid elongase increases significantly with the consumption of a diet with HLSO. SCD16 desaturase “activity” decreases with fat diet, while SCD18 desaturase “activity” increases. The level of SCD18 is significantly higher than the level of SCD16. Consumption of HLSO reduces the content of ω-3 PUFA in rat liver lipids, while the intake of HOSO increases it. Conclusions: HLSO diet reduces the endogenous biosynthesis of oleic and palmitic acids, as determined by the analysis of the rat liver NL fraction. A fat diet reduces SCD16 “activity” but increases SCD18 “activity”, especially when fed a diet with HOSO. The diet with HLSO reduces the content of ω-3 PUFA in liver lipids.